2010
DOI: 10.1016/s0377-1237(10)80043-7
|View full text |Cite
|
Sign up to set email alerts
|

Role of Prophylactic Antibiotics in Laparoscopic Cholecystectomy

Abstract: Background: Antibiotic prophylaxis is routinely administered in laparoscopic cholecystectomy but its role is debatable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 6 publications
1
21
0
Order By: Relevance
“…). After exclusions, a total of 19 studies remained with 5259 participants, of whom 2709 (51·5 per cent) were administered perioperative antibiotics. Table summarizes the design, sample sizes, setting, participants, interventions and outcomes of eligible studies published between 1997 and 2015.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…). After exclusions, a total of 19 studies remained with 5259 participants, of whom 2709 (51·5 per cent) were administered perioperative antibiotics. Table summarizes the design, sample sizes, setting, participants, interventions and outcomes of eligible studies published between 1997 and 2015.…”
Section: Resultsmentioning
confidence: 99%
“…Fifteen studies reported infections by postoperative day (POD) 30, and one by POD 7. Information regarding timing of the outcome was missing in three studies.…”
Section: Resultsmentioning
confidence: 99%
“…[6,[9][10][11] In a randomized controlled trial by Gaur et al on 417 patients undergoing laparoscopic cholecystectomy, an overall infection rate was 2.2%, which is consistent with the results obtained in our study. [12] In the present study, we had higher incidence of bile spillage (20%, n=48, N=240). Possible cause could be involvement of acute cases (10%) and different levels of operating surgeons, though all of them were experienced about the procedure.…”
Section: Discussionmentioning
confidence: 39%
“…Our results showed that the overall prevalence of bacteria within bile sampled at uncomplicated LC was 8.2% while it was 2.8% -25 % in different reported studies (7,(14)(15)(16). The lower rate of bactobilia has been reported among patients who underwent LC (2.8%), when compared to the overall rate of 13.3% in patients undergoing open cholecystectomy (7).…”
Section: Discussionmentioning
confidence: 45%
“…In one patient, we isolated acinetobacter the risk factor, and the possibility of this type of contamination related to the hospital, and it is not expected to be isolated from healthy non-hospitalized patients. It was shown recently that prolonged bile duct obstruction leads to an impaired intestinal wall barrier and as a result, bacteria can colonize bile easier, thus, it is not surprising that gramnegative enteric bacteria, especially E. coli, are the most common bacteria causing bactobilia in many studies including ours (13)(14)(15)(16)(17)(18). In our study, imipenem and aminoglycosides, especially amikacin, were the most effective antibiotics.…”
Section: Discussionmentioning
confidence: 81%